Surgical Options for Primary Synovial Chondromatosis of the Knee: A Systematic Review - Zhen Jonathan Liang, MBBS (Hons); Yu Liu, MBBS; Vachalam Rangasamie Danakkrisna, MBBS; Zi Qiang Glen Liau, MBBS, MRCS, MMed (Ortho), FRCS (Ortho), FAMS (Ortho), MBA (Arthroplasty Today)
Background: Synovial chondromatosis is a rare benign condition characterized by the formation of cartilaginous nodules within the synovium of joints, bursae, or tendon sheaths. While nonsurgical management exists, surgical intervention is often necessary. This systematic review aims to evaluate surgical options for managing synovial chondromatosis of the knee and compare recurrence rates following each procedure. Methods: Adhering to the Preferred Reporting Items of Systematic Review and Meta-Analysis guidelines, a literature search was conducted using PubMed, SCOPUS, and Embase, up to April 2025. Studies included detailed surgical interventions for primary synovial chondromatosis of the knee. Results: Thirty-seven studies met the inclusion criteria, comprising 30 case reports, 4 retrospective studies, and 3 case series, involving 120 patients (70 males, 49 females, 1 unspecified). Surgical techniques were categorized into open, arthroscopic, and combined approaches. Open approaches included arthrotomies without synovectomy, partial and total synovectomies, and total knee arthroplasty. Arthroscopic approaches involved washouts and synovectomies (partial and total). Combined approaches included staged surgeries with both open and arthroscopic techniques. Recurrence rates varied: open arthrotomy (0%; 1 and 20 year follow-up), arthroscopic synovectomy (5.71%; average follow-up duration 1.53 years), open synovectomy (12.5%; average follow-up 2.04 years), total knee arthroplasty (20.8% average follow-up 10.3 years), and arthroscopic washout (31.4%; average follow-up 6.56 years). Combined approaches reported no recurrences in 6 cases with average follow-up 1.44 years. Conclusions: This systematic review highlights variability in recurrence across techniques. Arthroscopic synovectomy and combined approaches demonstrated the lowest recurrence; however, the choice of surgical method should be tailored to the individual patient's condition and the surgeon's expertise.